Mobile Application Development for Management of Information System of Agro-Tourism Activities and Attractions with YII Framework - Buangam, Pornsin; Sriyom, Utumporn; Kanjanaklod, Waraporn; Atitang, Pattanun; Janwichian, Kunwadee; Sutthirak, Teachita (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Noppitam district, Nakhon Si Thammarat is known as one of Thailand’s rich natural sources which features a range of agro-tourist attractions. However, there is no dependable information system for management of tourism and routing guidance available in such district. The locals mostly resort to their own social media platforms in attempt to publicize local attractions, which unfortunately causes disorderliness to the information. Upon arrival at the Noppitam district, Nakhon Si Thammarat, tourists therefore have to search for information of each tourist attraction separately. Regarding this, it is essential to develop the management information system for agro-tourism activities and attractions with the YII framework, and implement the MySQL to devise the database. This can help with management of information for tourism, restaurants, and residences available around the district. Moreover, it can serve as the central system which provides tourists with information regarding tourist attractions open in the Noppitam district as well as guides them to the destinations, restaurants, and residences nearby, with accurate multilayered data on Google Maps API. The system also enables tourists to give feedback, either via their iOS or Android devices. Thanks to the participative data management, owners of attractions, restaurants, and residences can manually update information to keep it all up to date.